Penerapan Metode Bernyanyi dalam Meningkatkan Hasil Belajar Siswa pada Pembelajaran PAI Materi ( Asmaul Husna ) - Sarni Sarni; Irwanto Irwanto; Erlida Erlida (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2022)
This study aims to evaluate the effectiveness of the application of the singing method in improving student learning outcomes in Islamic Religious Education (PAI) subjects, with a special focus on the material of Asmaul Husna. The singing method was chosen because it is believed to create a more enjoyable and interactive learning atmosphere, so that students can more easily memorize and understand the Asmaul Husna. In this study, the approach used was quantitative with an experimental method. Data were collected through learning outcome tests conducted before and after the application of the singing method. The results showed a significant increase in student learning outcomes after this method was applied. Students seemed more enthusiastic and motivated in the learning process, and experienced significant progress in memorizing Asmaul Husna. In terms of memorization, there was a striking increase, from 40% to 85%, while in understanding, the results increased from 35% to 80%. Based on these findings, the singing method is recommended as an effective alternative to improve student learning outcomes in PAI subjects.